2021
DOI: 10.2147/jpr.s311557
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Korean Medicine as Collaborating Treatments with Conventional Treatments for Knee Osteoarthritis: A Protocol for a Systematic Review and Meta-Analysis

Abstract: Background: Knee osteoarthritis (OA) is a degenerative disease of the joint cartilage with no definite treatment in the early stage. Several previous review studies have shown that alternative medical treatments, including acupuncture, moxibustion, and herbal medicines, are effective in improving the symptoms of the disease and the patient's quality of life. However, no systematic review study has shown the effectiveness of the combination of conventional and alternative therapies. Therefore, the aim of our st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The last decade of research demonstrated that the formula of TCM has promising potency for handling OA (Li & Zhang, 2020; Park et al, 2021). In their study, Peng et al showed that 5,7,3′,4′‐tetramethoxyflavone restored cholesterol dysregulation by mediating SIRT1/FOXO3a/ABCA1 signaling in OA‐affected chondrocytes (Peng et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The last decade of research demonstrated that the formula of TCM has promising potency for handling OA (Li & Zhang, 2020; Park et al, 2021). In their study, Peng et al showed that 5,7,3′,4′‐tetramethoxyflavone restored cholesterol dysregulation by mediating SIRT1/FOXO3a/ABCA1 signaling in OA‐affected chondrocytes (Peng et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…reviewregistry1086, http://www.researchregistry.com) and is published as a research paper. [19] This study is written according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 checklist. [20]…”
Section: Methodsmentioning
confidence: 99%
“…4. Traditional Chinese medicine treatment, such as Chinese medicine ointment, massage, acupuncture and moxibustion, which are mainly used to improve blood circulation ( Walsh et al, 2017 ; Zhang Z. et al, 2020 ; Park et al, 2021 ). 5.…”
Section: Introductionmentioning
confidence: 99%